Deposition environment of organic sequences in Mae Teep coal mine implied by maceral characteristics - Piyatida Sangtong (2020)
© Suranaree University of Technology. This study is to assesses the depositional environment and characteristics of petroleum source rocks of Mae Teep basin in Lampang province, Thailand. The stratigraphic units included leonardite, coals, and oil shale units. A total of 44 samples were collected and subjected to petrological analysis for their maceral types. Additionally, the proximate and ultimate chemical analyses were performed. All results were used to interpret their deposition environments. The leonardite contains a high concentration of ash but low concentrations of organic matters, <15.00 wt%. The coal sub-units contain 10.40-68.48 wt% ash, 27.43-45.78 wt% volatile matter, and 3.16-46.31 wt%fixed carbon. The coals are classified as vitrinite (67.4-75.3%) and liptinite (11.9-23.2%). The liptinite is dominated by liptodetrinite, sporinite, cutinite, and fluorinite. The oil shale contains 49.59-83.85 wt% ash, 14.55-37.67 wt% volatile matter, and 0.55-12.74 wt% fixed carbon and short- and long-bodied lamalginite maceral dominated. The results indicated that fluctuation of the water levels had caused the depositional environment changes from a shallow swamp to reed-sedge peat, and from forest swamp to deep, stagnant, lacustrine deposits. The organic deposits settled in the basin through catastrophic fluvial flood events.